Traditional Chinese Medicine in the treatment of hemorrhoids—a review of preparations used and their mechanism of action - Zhou, Meng’en; Jin, Wenqi; Li, Peng; Wang, Ruolin; Guo, Xiutian (Frontiers in Pharmacology, 2023)
Hemorrhoids are a proctological disease primarily characterized by bleeding, prolapse, edema, and pain, severely affecting the quality of life. Surgery is an effective treatment for hemorrhoids, but the cost is relatively high, and complications such as difficulty in defecation, persistent pain, and heavy bleeding may occur postoperatively. Traditional Chinese Medicine (TCM) has a distinctive advantage in alleviating the clinical symptoms of hemorrhoid patients, reducing pain, and improving the quality of life. However, there are few summary literature about the mechanism of TCM in the prevention and treatment of hemorrhoids. Based on the etiology of hemorrhoids in both traditional Chinese and Western medicine, this paper reviews the recent research on the mechanism of TCM in the treatment of hemorrhoids, hoping to provide a basis for the better application of TCM in clinical and experimental research.